Modeling Interactions among Individual P2 Receptors to Explain Complex Response Patterns over a Wide Range of ATP Concentrations - Xing, Shu; Grol, Matthew W.; Grutter, Peter H.; Dixon, S. Jeffrey; Komarova, Svetlana V. (Frontiers in Physiology, 2016)
EExtracellular ATP acts on the P2X family of ligand-gated ion channels and several members of the P2Y family of G protein-coupled receptors to mediate intercellular communication among many cell types including bone-forming osteoblasts. It is known that multiple P2 receptors are expressed on osteoblasts (P2X2,5,6,7 and P2Y1,2,4,6). In the current study, we investigated complex interactions within the P2 receptor network using mathematical modeling. To characterize individual P2 receptors, we extracted data from published studies of overexpressed human and rodent (rat and mouse) receptors and fit their dependencies on ATP concentration using the Hill equation. Next, we examined responses induced by an ensemble of endogenously expressed P2 receptors. Murine osteoblastic cells (MC3T3-E1 cells) were loaded with fluo-4 and stimulated with varying concentrations of extracellular ATP. Elevations in the concentration of cytosolic free calcium ([Ca2+]i) were monitored by confocal microscopy. Dependence of the calcium response on ATP concentration exhibited a complex pattern that was not explained by the simple addition of individual receptor responses. Fitting the experimental data with a combination of Hill equations from individual receptors revealed that P2Y1 and P2X7 mediated the rise in [Ca2+]i at very low and high ATP concentrations, respectively. Interestingly, to describe responses at intermediate ATP concentrations, we had to assume that a receptor with a K1/2 in that range (e.g. P2Y4 or P2X5) exerts an inhibitory effect. This study provides new insights into the interactions among individual P2 receptors in producing an ensemble response to extracellular ATP.